2003
DOI: 10.1103/physrevb.67.184404
|View full text |Cite
|
Sign up to set email alerts
|

Spin waves in magnetic double layers with strong antiferromagnetic interlayer exchange coupling: Theory and experiment

Abstract: We present a simple approach based on continuum theory to calculate spin-wave frequencies in thin magnetic multilayers taking into account both the nonuniform static and dynamic magnetizations, which are present in systems with strong interlayer exchange coupling. The calculation includes in-plane static magnetization, the canted and twisted state, bilinear and biquadratic interlayer exchange coupling, and the dynamic dipolar coupling. Therefore, we are able to compute accurate spin-wave frequencies in strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…The frequency offset of the optic mode in the simulation is possibly caused by the presence of a significant twisting of the magnetization along the film normal in the real sample. This additional effect can be treated by a multilayer simulation as shown by Buchmeier et al [14].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency offset of the optic mode in the simulation is possibly caused by the presence of a significant twisting of the magnetization along the film normal in the real sample. This additional effect can be treated by a multilayer simulation as shown by Buchmeier et al [14].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency offset of the optic mode in the simulation is caused by the presence of a significant twisting of the magnetization along the film normal in the real sample. This additional effect can be treated by a multilayer simulation as shown by Buchmeier et al 17 The effect of the biquadratic coupling on the mode frequency has been studied theoretically by Layadi. 10 For antiferromagnetic coupling, two situations can arise.…”
Section: A Static Characterizationmentioning
confidence: 99%
“…25 The calculation of the magnetic ground state and the spin wave frequencies in the extended UTFA is described in detail in Ref. 25.…”
Section: Calculationmentioning
confidence: 99%
“…However, in our previous work (Ref. 25) we have shown that the UTFA approach can be easily extended in order to accurately describe the modes in thicker films. We thereby included also the exchange modes and the twisted ground state found in exchange springs and also in the case of very strong interlayer exchange coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation